2020
DOI: 10.1038/s41467-020-18176-3
|View full text |Cite|
|
Sign up to set email alerts
|

Environmental variability supports chimpanzee behavioural diversity

Abstract: Large brains and behavioural innovation are positively correlated, species-specific traits, associated with the behavioural flexibility animals need for adapting to seasonal and unpredictable habitats. Similar ecological challenges would have been important drivers throughout human evolution. However, studies examining the influence of environmental variability on within-species behavioural diversity are lacking despite the critical assumption that population diversification precedes genetic divergence and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 76 publications
3
69
1
Order By: Relevance
“…Some degree of group-level informational uniqueness may thereby be theoretically expected in an early hominin Pan-like state. There is also some support for this in field studies where substantial between-group variation in traditions has been found between chimpanzee communities (e.g., Whiten et al 1999Whiten et al , 2001Sanz and Morgan 2007;Schöning et al 2008;Lycett et al 2009;Boesch 2012;Koops et al 2015;van de Waal 2018;Kaufhold and Van Leeuwen 2019;Kalan et al 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Some degree of group-level informational uniqueness may thereby be theoretically expected in an early hominin Pan-like state. There is also some support for this in field studies where substantial between-group variation in traditions has been found between chimpanzee communities (e.g., Whiten et al 1999Whiten et al , 2001Sanz and Morgan 2007;Schöning et al 2008;Lycett et al 2009;Boesch 2012;Koops et al 2015;van de Waal 2018;Kaufhold and Van Leeuwen 2019;Kalan et al 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Since our results have demonstrated that recent genetic variation in chimpanzees contains little geographic structure on a broad scale, behavioural flexibility may also play an important evolutionary role in their adaptability to environmental heterogeneity 63 . Chimpanzees have diverse and variable behavioural repertoires 64,65 that often vary among nearby communities 66 , they utilize learned techniques to harvest otherwise unobtainable foods 67 and their bevavioural diversity increases with environmental variability 68 . Indeed, chimpanzees living in arid habitats employ specialized behaviours to regulate the thermal exposure 8 and spontaneously innovate novel behaviours in response to increased environmental complexity arising from anthropogenic pressures [69][70][71] .…”
Section: Discussionmentioning
confidence: 99%
“…food sources and many vary their diets significantly according to resource availability (e.g., Cercopithecus mitis: Coleman and Hill 2015). Many genera, including Cercopithecus and Pan, also alter their time budgets, activity levels, group size, and home range in different locations (Campera et al 2014;Fan et al 2013;Kalan et al 2020;Korstjens et al 2018;Zhou et al 2013). As these biological traits are not necessarily fixed in primates, the relationship between diet and environmental factors may be less clear than in other taxa in which biological trait filtering has been shown to be important, such as birds and butterflies (Hanspach et al 2015;Wittmann et al 2016).…”
Section: Discussionmentioning
confidence: 99%